Easy computer basics : Windows 8.1 edition - Miller, Michael, 1958- (Que, 2013)
Easy Computer Basics See it done. do it yourself. It's that Easy! Easy Computer Basics, Windows 8.1 Edition teaches you the fundamentals to help you get the most from your computer hardware and software. Fully illustrated steps with simple instructions guide you through each task, building the skills you need to perform the most common computer tasks. No need to feel intimidated; we'll hold your hand every step of the way. Learn how to... -- Set up and configure your new computer system -- Upgrade your computer with new hardware and software -- Use Microsoft Windows 8.1-and personalize it just for you -- Connect to the Internet for web surfing, email, Facebook, and listening to digital music -- View and edit digital photos -- Watch your favorite movies and TV shows online with Netflix and Hulu Plus -- Protect your family and your computer from viruses, spam, and spyware -- Set up a wireless home network, and share your Internet connection with multiple computers.